Design of 2D Porous Coordination Polymers Based on Metallacrown Units. Issue 19 (29th March 2016) - Atzeri, Corrado; Marchiò, Luciano; Chow, Chun Y.; Kampf, Jeff W.; Pecoraro, Vincent L.; Tegoni, Matteo
Abstract: A 12‐metallacrown‐4 (MC) complex was designed and employed as the building block in the synthesis of coordination polymers, one of which is the first permanently porous MC architecture. The connection of the four‐fold symmetric MC subunits by Cu II nodes led to the formation of 2D layers of metallacrowns. Channels are present in the crystalline architecture, which exhibits permanent porosity manifested in N2 and CO2 uptake capacity. Abstract : Permanently porous metallacrowns : Metallacrowns have been exploited for the first time as tailored building blocks for the construction of new (porous) coordination polymers. Metallacrowns are metal‐rich complexes that have exhibited excellent properties in magnetism and luminescence. Benefiting from high‐interest metallacrown building blocks in the synthesis of MOFs can unfold a whole new class of functional materials (see figure).